Molecular cloning and characterization of the germline-restricted chromosome sequence in the zebra finch - Itoh, Yuichiro (2009)
The zebra finch (Taeniopygia guttata) germline-restricted chromosome (GRC) is the largest chromosome and has a unique system of transmission in germ cells. In the male, the GRC exists as a single heterochromatic chromosome in the germline and is eliminated from nuclei in late spermatogenesis. In the female, the GRC is bivalent and euchromatic and experiences recombination. These characteristics suggest a female-specific or female-beneficial function of the GRC. To shed light on the function of GRC, we cloned a portion of the GRC using random amplified polymorphic DNA-polymerase chain reaction and analyzed it using molecular genetic and cytogenetic methods. The GRC clone hybridized strongly to testis but not blood DNA in genomic Southern blots. In fluorescent in situ hybridization analysis on meiotic chromosomes from synaptonemal complex spreads, the probe showed hybridization across a large area of the GRC, suggesting that it contains repetitive sequences. We isolated a sequence homologous to the GRC from zebra finch chromosome 3 and a region of chicken chromosome 1 that is homologous to zebra finch chromosome 3; the phylogenetic analysis of these three sequences suggested that the GRC sequence and the zebra finch chromosome 3 sequence are most closely related. Thus, the GRC sequences likely originated from autosomal DNA and have evolved after the galliform-passeriform split. The present study provides a foundation for further study of the intriguing GRC.